SCDA task force on a special care dentistry residency. (26th April 2016) - Hicks, Jeffery; Vishwanat, Lakshmi; Perry, Maureen; Messura, Judith; Dee, Kristin
ABSTRACT: The Special Care Dentistry Association (SCDA) has acted on a proposal regarding the status of training in the care of patients with special needs. Two phases of action were undertaken. Phase 1: (a) examination of the literature on existing training and curricula in the care of patients with special needs and (b) a survey of existing postdoctoral programs in special needs. Phase 2: establish a group of experts who: (a) submitted to the Commission on Dental Accreditation a request to approve a postdoctoral general dentistry residency program in Special Care Dentistry and (b) created suggested accreditation standards for such postdoctoral programs. This article describes efforts by the SCDA to evaluate: The status of existing training of dental students in the care of patients with special needs. The number and characteristics of postdoctoral general dentistry programs offering formal training in the care of patients with special needs. Whether additional training in the care of patients with special needs is needed for dental students and dentists. Possible actions by SCDA to impact the numbers of dentists trained each year in the care of patients with special needs.